Smart system for monitoring electrical power usage at homes - Rahman, Kawthar; Abdul Muthalif, Asan Gani; Shua'ib, Nurul F. (IIUM Press, 2011)
Global warming and its disasters environmental and economic effects are considered as one of the major challenges that mankind will face during this century. Therefore, green technologies are very needed nowadays to reduce global warming. The smart device proposed in this chapter can help environment in reducing carbon footprint and save energy consumption at homes. Malaysia is now in mission towards “Green Earth” so any smart green technologies which may corresponds to this mission will get much of the attention worldwide. Smart home system functionality is dividing into the following five components which are sensor system, signal transmission systems, power transmission system, action system and central control system. Sensory system work having the responsibility to collect data. Whereas, power transmission is responsible for the various parts of the power supply, refers primarily to electric doors and windows, curtains, electrical switches and other actions to complete the module terminal and lastly the most central part of the central control system